2003
DOI: 10.1016/s0028-3932(02)00145-8
|View full text |Cite
|
Sign up to set email alerts
|

Beauty in a smile: the role of medial orbitofrontal cortex in facial attractiveness

Abstract: The attractiveness of a face is a highly salient social signal, influencing mate choice and other social judgements. In this study, we used event-related functional magnetic resonance imaging (fMRI) to investigate brain regions that respond to attractive faces which manifested either a neutral or mildly happy face expression. Attractive faces produced activation of medial orbitofrontal cortex (OFC), a region involved in representing stimulus-reward value. Responses in this region were further enhanced by a smi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

76
617
6
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 793 publications
(719 citation statements)
references
References 52 publications
76
617
6
10
Order By: Relevance
“…Previous studies have demonstrated that the motivational salience of attractive faces is variable by showing that other types of facial cue (e.g., emotional expression or gaze direction) can modulate responses to physically attractive versus physically unattractive faces in brain regions involved in motivation and reward processing (Kampe et al, 2001;O'Doherty et al, 2003). Here we present new evidence that the motivational salience of physically attractive faces is variable, finding that within-woman changes in hormone levels also modulate the motivational salience of physically attractive faces.…”
Section: Discussionmentioning
confidence: 49%
“…Previous studies have demonstrated that the motivational salience of attractive faces is variable by showing that other types of facial cue (e.g., emotional expression or gaze direction) can modulate responses to physically attractive versus physically unattractive faces in brain regions involved in motivation and reward processing (Kampe et al, 2001;O'Doherty et al, 2003). Here we present new evidence that the motivational salience of physically attractive faces is variable, finding that within-woman changes in hormone levels also modulate the motivational salience of physically attractive faces.…”
Section: Discussionmentioning
confidence: 49%
“…Similar results in the amygdala, which together with the OFC constitutes part of the structural appetitive/approach network that underpins Pavlovian incentive and motivated behavior (Gottfried et al, 2003;O'Doherty et al, 2003), and is commonly associated with regulation of emotion (Hare et al, 2005), lend further support for greater task-related emotional suppression or similar competing, extraneous or idiosyncratic factors operating in the "flat" cocaine subgroup. However, because the current correlation between SSG-R and OFC/IFG was driven by the "non-flat" cocaine group (and not the "flat" cocaine group), this interpretation remains tentative.…”
Section: The Ofc/ifg In the Constrained Subjective Sensitivity To Relmentioning
confidence: 62%
“…The pleasurable smiles associated with positive emotion have been shown to be a form of social reward (O'Doherty et al, 2003). Receiving these types of smiles is related to positive emotion (Cappella, 1997) and reciprocal smiling be- havior (Fridlund, 1991).…”
Section: Discussionmentioning
confidence: 99%